2008
DOI: 10.1038/nrmicro1998
|View full text |Cite
|
Sign up to set email alerts
|

CD4 immunophenotyping in HIV infection

Abstract: The ability to rapidly identify immune cell subsets such as CD4 cells, which became possible around the same time as the onset of the HIV/AIDS pandemic, was one of the greatest advances in clinical and diagnostic immunology. The evolution of this global pandemic and the subsequent development of treatment strategies to prolong the life of infected individuals mean that it is now more crucial than ever that we develop affordable, reliable and accurate methods for the enumeration of CD4 cells. Here, we provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 76 publications
2
55
0
1
Order By: Relevance
“…As a result, immunophenotyping of lymphocyte subsets by flow cytometry has been an indispensable tool in the management of HIV and AIDS patients. Various studies have shown that the reference ranges of lymphocyte subsets are subject to influences by age, sex, ethnicity, and environment (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Flow cytometry is the "gold standard" for the enumeration of lymphocyte subsets, and it is important to establish the local reference ranges for interpretation of laboratory results and clinical decision making (13).…”
mentioning
confidence: 99%
“…As a result, immunophenotyping of lymphocyte subsets by flow cytometry has been an indispensable tool in the management of HIV and AIDS patients. Various studies have shown that the reference ranges of lymphocyte subsets are subject to influences by age, sex, ethnicity, and environment (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Flow cytometry is the "gold standard" for the enumeration of lymphocyte subsets, and it is important to establish the local reference ranges for interpretation of laboratory results and clinical decision making (13).…”
mentioning
confidence: 99%
“…Separating pure cell subpopulations from the mixture of cells in blood is often the first step of a wide spectrum of research and clinical applications, including cell enumeration 1 , cell functional assays 2 , and cell-based therapies 3 . For human immunodeficiency virus (HIV) infected patients the number of CD4+ T lymphocytes in peripheral blood is an important maker for monitoring disease progression to AIDS and treatment efficacy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…These limitations restricted CD4 testing to national reference laboratories located mainly in capital or larger cities. The centralized laboratory model found in most countries meant that HIV patients had to travel long distances or rely on sample courier services to access laboratory services (5,6). The decentralized approach was made possible through the availability of user simplified flow-based platforms.…”
Section: Introductionmentioning
confidence: 99%